2009
DOI: 10.1177/1352458509106228
|View full text |Cite
|
Sign up to set email alerts
|

Brain abnormalities in Sjogren syndrome with recurrent CNS manifestations: association with neuromyelitis optica

Abstract: This study demonstrates that SS patients with recurrent CNS involvement have brain abnormalities characteristic of NMO and AQP4-Ab in Korea. The presence of AQP4-Ab in one SS patient with only brain involvement may suggest that the coexistence of NMO should be explored in SS patients with recurrent CNS manifestations, even without optic neuritis or myelitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
46
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(49 citation statements)
references
References 28 publications
2
46
1
Order By: Relevance
“…LM is a characteristic finding in NMO/NMOSD and its presence may be used to differentiate from myelitis in classic MS, which rarely extends beyond a single vertebral segment (33). Longitudinal cord involvement has been reported in SLE and SS as well (7,8,14,17,22,23,30,34,35). These reports have identified a high prevalence of the NMO-IgG antibody and additional features consistent with concurrent NMO/NMOSD in these patients.…”
Section: Discussionmentioning
confidence: 81%
“…LM is a characteristic finding in NMO/NMOSD and its presence may be used to differentiate from myelitis in classic MS, which rarely extends beyond a single vertebral segment (33). Longitudinal cord involvement has been reported in SLE and SS as well (7,8,14,17,22,23,30,34,35). These reports have identified a high prevalence of the NMO-IgG antibody and additional features consistent with concurrent NMO/NMOSD in these patients.…”
Section: Discussionmentioning
confidence: 81%
“…The association between myelopathy and systemic diseases, such as SLE and SS, is well recognized [30,31]. However, a recent study has suggested that NMOsd, SS, and SLE might be overlapping disorders that can coexist in some patients [8].…”
Section: Discussionmentioning
confidence: 99%
“…9,16 To our knowledge, two cases of pSS and NMOSD that were positive for AQP4 antibodies with only cerebral white matter lesions have been reported to date, and one was proven by brain biopsy to be more compatible with NMOSD than with pSS. 14,17 Our patient satisfied the 2012 classification criteria for pSS, 18 and her minor salivary gland biopsy showed typical histopathologic findings of pSS.…”
Section: Discussionmentioning
confidence: 61%
“…6 The coexistence of NMOSD and pSS is increasingly being reported, and most cases present with optic neuritis or transverse myelitis, making them more easily recognizable. 7,10,14,15 Cases of pSS with NMOSD that present with symptomatic cerebral white matter lesions, without optic neuritis or myelitis, are rare and hard to diagnose. In addition, although the anti-SSA/Ro antibody is frequently detected in patients with NMOSD, one series reported that only 2% of patients with NMOSD met the criteria for pSS.…”
Section: Discussionmentioning
confidence: 99%